EFEKTIFITAS CERITA PENDEK SEBAGAI MEDIA KAMPAYE “STOP BULLYING” TERHADAP SISWA SMP DIKOTA MAKASSAR: FUNGSI EDUKATIF KARYA SASTRA - Soraya, Andi Inayah; Badaruddin, M. Syafri (Universitas Hasanuddin, 2019)
This study aims to: 1) Know the effectiveness of short story in educating secondary school students in Makassar about bullying at school 2) Know the students responds toward moral values which exist in selected short stories. To limit this study, the researcher focused on the increasing of student’s ability in understanding kinds of bullying, bullying affects, and what they should do in facing bullying at school. The design of this study is quasi-experimental using one group design (pre test and post test). The respondents in this research are 206 students from three (3) of secondary schools; SMP 8, SMP 12, and SMP Islam Athira Makassar. Based on Wilcoxon Signed Rank Test the researcher found the data which 203 students (99%) scoring post-test > pre-test, 3 students (1%) scoring post-test = pretest, and p-value 0,00. It means the p-value < 0,05 so Ho was rejected and the researcher concluded that there is significant improvement between pre-test and post-test. Based on interviewing the students responds toward moral values which exist in selected short stories the researcher found that there is positive reception where students are able to classified kinds of bullying, the effect of bullying, and what they should do in facing bullying at school.